A sponge oil-absorbing material loaded with biochar and bentonite, and preparation method and application thereof

Through sponge oil-absorbing materials loaded with biochar and bentonite, the problems of low efficiency, high cost and poor material durability of petroleum hydrocarbon pollution treatment in the prior art are solved, and efficient and low-cost oil-water separation and recovery effects are achieved.

CN116510683BActive Publication Date: 2025-03-11崇左南方水泥有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310728727.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-03-11
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

In the prior art, when dealing with petroleum hydrocarbon pollution in water, there are problems such as low efficiency, high cost, complex operating conditions and poor material durability.

Method used

A sponge oil-absorbent material loaded with biochar and bentonite is used to modify the polyurethane sponge by dopamine hydrochloride, and biochar and bentonite are used as loaded particles, and super hydrophobic and lipophilic sponge oil-absorbent material is prepared by modifying it with silane coupling agent.

Benefits of technology

It has achieved excellent oil adsorption capacity and good mechanical properties for petroleum hydrocarbon pollutants in the water. The preparation method is simple, low-cost, good recycling performance, and can be efficiently recovered and utilized in different oil and water mixtures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116510683B_ABST
    Figure CN116510683B_ABST
Patent Text Reader

Abstract

The present invention discloses a sponge oil-absorbing material loaded with biochar and bentonite, and a preparation method and application thereof, and belongs to the field of environmental pollution control. The present invention utilizes the self-polymerization and strong adhesion of dopamine to bond biochar and bentonite to a polyurethane sponge, and then uses a silane coupling agent to perform hydrophobic and lipophilic modification on the loaded biochar-bentonite polyurethane sponge. The biochar loaded by the sponge oil-absorbing material is burned by fir sawdust, and the bentonite is purified sodium-based bentonite, which is not easy to produce secondary pollution during actual use. The sponge oil-absorbing material of the present invention is used for the treatment of petroleum hydrocarbon pollution in water, has excellent oil adsorption capacity and good mechanical properties, has a simple preparation method, low cost, good recycling performance, and can achieve efficient recovery and utilization of different oil-water mixtures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental pollution control, and in particular relates to a sponge oil-absorbing material loaded with biochar and bentonite, and a preparation method and application thereof. Background Art

[0002] With the rapid development of urban industrialization, total petroleum hydrocarbons (PHs) inevitably leak into groundwater, rivers, lakes and oceans during industrial production and oil extraction, transportation and use. The ecotoxicity and bioaccumulation of PHs have brought serious pollution problems to the water environment. Due to its low density, oil can float on the water surface, thus blocking air and light, and the biotransformation of oil is usually very slow, leading to the death of aquatic organisms.

[0003] Research on durable superhydrophobic materials has become a hot topic in the field of oil-water separation and oil spill cleanup. The current methods for separating oil-water mixtures mainly include skimming, gravity separation, centrifugation, flotation, bioremediation and on-site burning. However, these traditional oil spill cleanup methods inevitably have shortcomings such as low efficiency, secondary environmental pollution, high cost, long cycle and complex operating conditions. Therefore, it is very urgent to develop efficient, fast and low-cost oil-water separation materials.

[0004] The key to permeable reactive wall repair technology lies in the medium material, the application of the medium material, and the effect analysis: Various adsorbent materials have recently been used as the preferred method for cleaning petroleum pollutants and waste oils due to their high selectivity, environmental friendliness, chemical inertness, low operating cost, strong absorption capacity, and easy recovery. Although porous absorbents such as zeolite, porous polymers, activated carbon, carbon aerogel, wood, clay, sugarcane bran and straw are widely used as oil absorbents, they have problems with low absorption rate, selectivity and recyclability. Compared with many materials, sponges are very effective in treating oil pollution. Polyurethane (PU) sponge is a new type of sponge with low density and high performance. High-porosity polyurethane sponge materials have the advantages of large surface area, high oil absorption rate, fast adsorption rate, and easy recovery. Because polyurethane molecules contain a large number of polar bonds, they are both hydrophilic and lipophilic, and the oil-water selectivity of the material is poor, so it cannot be used directly as an oil-absorbing material. It is necessary to modify the structure of traditional PU materials to improve the oil absorption performance of sponges. By constructing the surface morphology of the sponge matrix material and introducing low surface energy substances, hydrophobic and oleophilic sponge materials can be prepared.

[0005] In recent years, inspired by the adhesion function of marine mussels, mussel biomimetic chemistry has gradually developed. Through the construction of micro-nanostructures by dopamine surface modification, and the combination of long-chain alkyl compounds and other substances to reduce surface energy, super hydrophobic and lipophilic materials can be prepared. However, the construction of a simple dopamine nanosurface or the addition of additional nanoparticles is easily damaged by external forces, resulting in a weakening or even a significant reduction in the super hydrophobic and lipophilic properties of the material. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a sponge oil-absorbing material loaded with biochar and bentonite, and a preparation method and application thereof. With a low-priced polyurethane sponge as a matrix, the polyurethane sponge modified with dopamine hydrochloride is immersed in a suspension prepared with bentonite and biochar with good adsorption capacity, and the bentonite and biochar are used as the loading particles of the polyurethane sponge. After modification with a silane coupling agent, a super-hydrophobic and oleophilic polyurethane sponge is obtained. The prepared sponge oil-absorbing material is used for the treatment of petroleum hydrocarbon pollution in water, has excellent oil adsorption capacity and good mechanical properties, has a simple preparation method, low cost, good recycling performance, and can realize efficient recovery and utilization of different oil-water mixtures.

[0007] To achieve the above object, the present invention provides a sponge oil-absorbing material loaded with biochar and bentonite, comprising a polyurethane sponge, dopamine hydrochloride, and biochar and bentonite loaded on the polyurethane sponge.

[0008] Preferably, the biochar is fir sawdust biochar, and the bentonite is purified sodium-based bentonite.

[0009] The fir sawdust biochar is made by burning fir sawdust at 300-600°C and passing through a 100-200 mesh sieve. Advantages of using fir sawdust biochar: Fir sawdust biochar has the advantages of large specific surface area, rich functional groups and good stability. Fir sawdust is used to modify the polyurethane material. After adding fir sawdust biochar, the effective adsorption sites on the surface of the polyurethane sponge increase, the surface area increases, and the adsorption effect is enhanced.

[0010] The preparation method of the purified sodium-based bentonite comprises the following steps: dissolving 50-100g of natural sodium-based bentonite into 500-800mL of ultrapure water, stirring continuously for 2-4h to make it dispersed evenly to form a suspension; after the stirring is completed, the bentonite suspension is allowed to stand for 20-40min, after the standing is completed, the upper suspension is centrifuged; after the centrifugation is completed, the precipitate is placed at 50-60°C for drying, after the drying is completed, the precipitate is crushed and passed through a 100-200 mesh sieve to obtain purified sodium-based bentonite. Bentonite is a clay mainly composed of montmorillonite. Natural bentonite is generally calcium-based bentonite, and its physical and chemical properties are not ideal and there are many impurities. All components other than montmorillonite are impurities and must be separated. After the natural bentonite is purified, its adsorption, specific surface area, and dispersibility can be greatly improved, and the purified bentonite can significantly broaden its application performance and application field.

[0011] A method for preparing the sponge oil-absorbing material loaded with biochar and bentonite comprises taking a polyurethane sponge as a matrix, modifying it with dopamine hydrochloride, then loading biochar and bentonite, and modifying it with a silane coupling agent to obtain the sponge oil-absorbing material loaded with biochar and bentonite.

[0012] Preferably, the polyurethane sponge is pretreated before being modified with dopamine hydrochloride. The pretreatment process is as follows: the polyurethane sponge is ultrasonically cleaned 2 to 4 times in anhydrous ethanol and deionized water in turn. After cleaning, the cleaned polyurethane sponge is dried at 50 to 60° C. for 10 to 12 hours.

[0013] More preferably, the commercially available polyurethane sponge is cut into a rectangular block with a thickness of no more than 1 cm and a side length of no more than 2 cm; and the block is ultrasonically cleaned in anhydrous ethanol or deionized water for 2 to 4 hours.

[0014] Preferably, the process of modification using dopamine hydrochloride is as follows: adding dopamine hydrochloride to an alkaline buffer solution, adjusting the pH value of the solution to 8.0-9.0, and obtaining a dopamine hydrochloride-alkaline buffer solution; then soaking the pretreated polyurethane sponge in the dopamine hydrochloride-alkaline buffer solution at room temperature for 10-20 hours, and after the soaking is completed, taking out the polyurethane sponge, and rinsing the unreacted dopamine hydrochloride with ultrapure water to obtain a dopamine-coated polyurethane sponge.

[0015] Preferably, the material-liquid ratio of dopamine hydrochloride to alkaline buffer solution is (0.01-0.05) g: (50-100) mL;

[0016] The alkaline buffer solution is a tris(hydroxymethyl)aminomethane buffer (Tris buffer) with a concentration of 10-20 mmol / L.

[0017] Preferably, the process of loading biochar and bentonite is as follows: add biochar and bentonite into water, mix to obtain a biochar-bentonite mixed solution, immerse a dopamine-coated polyurethane sponge in the biochar-bentonite mixed solution, squeeze out the solution after the sponge is saturated with adsorption, and repeat this immersion-extrusion process 3 to 5 times; the sponge after immersion-extrusion is dried at 50 to 60° C. for 10 to 12 hours to obtain a biochar-bentonite loaded sponge.

[0018] Preferably, the mass ratio of biochar to bentonite is 1:1 to 1:5.

[0019] Preferably, the process of modification with silane coupling agent is as follows: soaking the biochar-bentonite loaded sponge in silane coupling agent for 1 to 2 hours to obtain the sponge oil-absorbing material loaded with biochar and bentonite.

[0020] Preferably, the silane coupling agent is one of hexadecyltrimethoxysilane, dodecyltrimethoxysilane, methyltrimethoxysilane and trichlorooctadecylsilane, and the volume concentration of the silane coupling agent is 0.5-3%.

[0021] Application of the sponge oil-absorbing material loaded with biochar and bentonite in oil-water separation.

[0022] Preferably, the sponge oil-absorbing material loaded with biochar and bentonite is used to absorb petroleum hydrocarbon pollutants in water, such as organic solvents (straight-chain alkanes, branched-chain alkanes) and oil products (engine oil, edible oil, etc.). When the sponge oil-absorbing material is used, it is directly put into water containing petroleum hydrocarbon pollutants for adsorption for 10 to 30 seconds. After the petroleum hydrocarbon pollutants are adsorbed, the sponge oil-absorbing material can be directly taken out.

[0023] Based on mussel biomimetic chemistry, the surface of the block material is modified with dopamine hydrochloride, and then other particles are loaded in the block material. When encountering strong acid and alkali or complex oil-water environment, the durability of the material is poor. The sponge oil-absorbing material prepared by the present invention is prepared by co-modification of biochar, bentonite and dopamine hydrochloride. In the present invention, a polyurethane sponge is first reacted with dopamine hydrochloride to obtain a dopamine-coated sponge, and then biochar, bentonite and a silane modifier are uniformly mixed to obtain a suspension, and the polyurethane sponge modified by dopamine hydrochloride is completely immersed in the above suspension, and is closely combined with the polyurethane sponge loaded with biochar and bentonite through the action of hydroxyl, and then the sponge is hydrophobically modified by a silane coupling agent, so that the sponge oil-absorbing material loaded with biochar and bentonite can be obtained, which solves the problem of poor durability of the material when encountering strong acid and alkali or complex oil-water environment.

[0024] Since the oil-absorbing material will eventually be placed in the actual environment for oil-water adsorption and separation, the pH of the actual water body may vary greatly due to the influence of the leaked chemicals at the same time. Therefore, the present invention has conducted a corrosion resistance test on the silane-modified sponge material in a wide pH range (1 to 13). The results show that natural sodium-based bentonite is alkaline, montmorillonite and quartz in bentonite have certain acid and alkali resistance, and fir sawdust biochar also has the characteristics of acid and alkali corrosion resistance. Since polydopamine is a high temperature and acid and alkali resistant material, biochar and bentonite are added to the sponge through polydopamine, which enhances the acid and alkali resistance of the sponge and makes its application more extensive.

[0025] Compared with the prior art, the present invention has the following advantages and technical effects:

[0026] 1) The preparation method of the present invention is simple, low-cost, does not require multi-step modification operations, and does not contain toxic hydrophobic modification reagents such as fluorine or chlorine, and is not prone to secondary pollution when treating petroleum hydrocarbon pollutants in water;

[0027] 2) The present invention uses commercially available polyurethane sponge as the base material, retains the original porous network structure of the sponge, does not undergo significant deformation due to multiple extrusions, and has good mechanical properties;

[0028] 3) The biochar and bentonite-loaded sponge oil-absorbing material prepared by the present invention can continuously, rapidly and selectively absorb organic solvents and waste oil products in sewage, and has good hydrophobic and lipophilic properties.

[0029] 4) The biochar and bentonite-loaded sponge oil-absorbing material prepared by the present invention is a dark brown block material with good adsorption performance for oil products. At the same time, it has good hydrophobicity and continuous oil absorption capacity, and can realize efficient recovery and utilization of different oil-water mixtures. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0031] Figure 1 These are scanning electron micrographs of the cleaned polyurethane sponge, dopamine-coated polyurethane sponge, and hydrophobic and oleophilic sponge oil-absorbing materials loaded with biochar and bentonite in Example 1, including: (a) cleaned polyurethane sponge (PU), (b) dopamine-coated polyurethane sponge (PDA / PU), (c) a partial enlarged view of dopamine-coated polyurethane sponge (PDA / PU), and (d) hydrophobic and oleophilic sponge oil-absorbing material loaded with biochar and bentonite (PDA / BC / BT / PU).

[0032] Figure 2This is a comparison diagram of the oil-water contact angles of the hydrophobic and oleophilic sponge oil-absorbing materials loaded with biochar and bentonite in Example 1.

[0033] Figure 3 It is the Fourier infrared spectra of the fir sawdust biochar (BC), purified sodium bentonite (BT), cleaned polyurethane sponge (PU), dopamine-coated polyurethane sponge (PDA / PU), and hydrophobic and lipophilic sponge oil-absorbing material loaded with biochar and bentonite (PDA / BC / BT / PU) in Example 1.

[0034] Figure 4 This is a contact angle change diagram of the hydrophobic and oleophilic sponge oil-absorbing material (PDA / BC / BT / PU) loaded with biochar and bentonite in Example 1 after being immersed in a solution with a pH value of 1 to 13 for 24 hours.

[0035] Figure 5 This is a graph showing the reuse performance of the hydrophobic and oleophilic sponge oil-absorbing material (PDA / BC / BT / PU) loaded with biochar and bentonite in Example 1 for n-hexane. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0041] The normal temperature in the embodiment of the present invention refers to 25±2°C.

[0042] The polyurethane sponge in the embodiment of the present invention was purchased from Zhejiang Freda Sponge Co., Ltd., and the natural sodium-based bentonite was purchased from Tianjin Bailuns Biotechnology Co., Ltd.

[0043] Example 1

[0044] Step (1), cutting a commercially available polyurethane sponge into a 2×2×1 cm rectangular block, then ultrasonically cleaning the polyurethane sponge in anhydrous ethanol and deionized water for 3 times, and after cleaning, drying the cleaned polyurethane sponge in a 60° C. oven for 10 h.

[0045] Step (2), adding 0.05 g of dopamine hydrochloride to 50 mL of 10 mmol / L Tris alkaline buffer solution, adjusting the pH value of the solution to 8.5, to obtain a dopamine hydrochloride-Tris solution; then soaking the polyurethane sponge in the dopamine hydrochloride-Tris solution at room temperature for 12 hours. After the soaking is completed, taking out the polyurethane sponge, rinsing the unreacted dopamine hydrochloride with ultrapure water, to obtain a dopamine-coated polyurethane sponge.

[0046] Step (3), sintering fir wood chips at 400°C and passing through a 200-mesh sieve to obtain fir wood chip biochar; dissolving 50 g of natural sodium bentonite in 700 mL of ultrapure water, stirring continuously for 3 hours to disperse it evenly to form a suspension, and after the stirring is completed, the bentonite suspension is allowed to stand for 30 minutes. After the standing is completed, the upper suspension is centrifuged. After the centrifugation is completed, the precipitate is placed at 60°C for drying. After the drying is completed, the precipitate is crushed and passed through a 200-mesh sieve to obtain purified sodium bentonite.

[0047] Step (4), adding fir sawdust biochar and the purified sodium bentonite prepared in step (3) in a mass ratio of 1:1 into 50 mL of ultrapure water for mechanical mixing, stirring at room temperature for 2 hours to obtain a uniformly dispersed biochar-bentonite mixture; immersing a dopamine-coated polyurethane sponge in the biochar-bentonite mixture, squeezing out the solution after the sponge is saturated with adsorption, and repeating this immersion-extrusion process 5 times; placing the sponge after immersion-extrusion in an oven at 60°C and drying it for 10 hours to obtain a biochar-bentonite loaded sponge.

[0048] Step (5), measure 0.5 mL of hexadecyltrimethoxysilane (HDTMS) and 49.5 mL of anhydrous ethanol in a beaker, prepare a silane-modified liquid with a volume concentration of 1%, soak the biochar-bentonite loaded sponge in the above 1% HDTMS modified liquid for 2 hours, and obtain a hydrophobic and lipophilic sponge oil-absorbing material loaded with biochar and bentonite.

[0049] The scanning electron micrographs of the washed polyurethane sponge, dopamine-coated polyurethane sponge, and the hydrophobic and oleophilic sponge oil-absorbing materials loaded with biochar and bentonite in Example 1 are shown in FIG. Figure 1 , (a) is a scanning electron microscope image of the cleaned polyurethane sponge in Example 1. Using a scanning electron microscope, it can be observed that the cleaned polyurethane sponge has a multi-layer pore network structure and a smooth surface; (b) is a scanning electron microscope image of the dopamine-coated polyurethane sponge prepared in Example 1; (c) is a local enlarged image of the dopamine-coated polyurethane sponge (PDA / PU). It can be observed that the surface of the dopamine-coated polyurethane sponge in Example 1 has a certain degree of roughness, maintaining the original three-dimensional porous structure, and the sponge skeleton is covered with fine dopamine particles; (d) is a scanning electron microscope image of the hydrophobic and oleophilic biochar and bentonite-loaded sponge oil-absorbing material prepared in Example 1. It can be observed that the surface of the biochar-bentonite-loaded sponge in Example 1 is rough, and the biochar and bentonite are successfully adhered to the sponge, constructing a rough structure for the sponge.

[0050] Figure 2 It is a comparison diagram of the oil-water contact angles of the hydrophobic and oleophilic sponge oil-absorbing materials loaded with biochar and bentonite in Example 1; from the test of the contact angle measuring instrument, it can be seen that the water contact angle of the hydrophobic and oleophilic sponge oil-absorbing materials loaded with biochar and bentonite is 128°.

[0051] Figure 3 The Fourier infrared spectra of fir sawdust biochar, purified sodium bentonite, cleaned polyurethane sponge, dopamine-coated polyurethane sponge, hydrophobic and oleophilic sponge oil-absorbing materials loaded with biochar and bentonite in Example 1 are shown in Figure 1. -1 and 2920cm -1 The stretching vibration peaks of OH and the bending vibration peaks of CH are found at 4000-3500 cm-1 The absorption peak between them is the hydroxyl stretching vibration absorption peak in Al—O—H, 3434 cm -1 The absorption peak at 1632 cm is the hydroxyl stretching vibration absorption peak of water in the interlayer structure of bentonite. -1 The absorption peak at 1019 cm is the O—H bending vibration absorption peak of interlayer water molecules. -1 The absorption peak at 1715cm is the stretching vibration absorption peak of octahedral Si—O—Si in the bentonite lattice. -1 The absorption peak at 1542cm is the C=O stretching vibration peak. -1 The peaks at 2926cm are N—H stretching vibration peaks, which are characteristic absorption peaks of polyurethane sponge. -1 The adsorption peak at 1493 cm -1 and 1264cm -1 The characteristic peaks at are caused by the NH bending vibration and CO bending vibration in the PDA molecule. The above analysis shows that dopamine, biochar and bentonite are successfully loaded on the polyurethane sponge.

[0052] Example 2

[0053] Step (1), cutting a commercially available polyurethane sponge into a 2×2×1 cm rectangular block, then ultrasonically cleaning the sponge in anhydrous ethanol and deionized water for 4 times, and after cleaning, drying the cleaned polyurethane sponge in a 50° C. oven for 12 h.

[0054] Step (2), adding 0.01 g of dopamine hydrochloride to 100 mL of 10 mmol / L Tris alkaline buffer solution, adjusting the pH value of the solution to 8.0, to obtain a dopamine hydrochloride-Tris solution; then soaking the cleaned polyurethane sponge in the dopamine hydrochloride-Tris solution at room temperature for 20 hours. After the soaking is completed, taking out the polyurethane sponge, rinsing the unreacted dopamine with ultrapure water, to obtain a dopamine-coated polyurethane sponge.

[0055] Step (3), sintering fir wood chips at 300°C and passing through a 100-mesh sieve to obtain fir wood chip biochar; dissolving 100 g of natural sodium bentonite in 800 mL of ultrapure water, stirring continuously for 4 hours to disperse it evenly to form a suspension, and after the stirring is completed, the bentonite suspension is allowed to stand for 40 minutes. After the standing is completed, the upper suspension is centrifuged. After the centrifugation is completed, the precipitate is placed at 50°C for drying. After the drying is completed, the precipitate is crushed and passed through a 100-mesh sieve to obtain purified sodium bentonite.

[0056] Step (4), adding fir sawdust biochar and purified sodium bentonite in a mass ratio of 1:5 into 50 mL of ultrapure water for mechanical mixing, stirring at room temperature for 2 hours to obtain a uniformly dispersed biochar-bentonite mixture; immersing a dopamine-coated polyurethane sponge in the biochar-bentonite mixture, squeezing out the solution after the sponge is saturated with adsorption, and repeating this immersion-extrusion process 5 times; the sponge after immersion-extrusion is placed in a 50°C oven and dried for 12 hours to obtain a biochar-bentonite loaded sponge.

[0057] Step (5), measuring 1.5 mL of trichlorooctadecylsilane and 49.5 mL of anhydrous ethanol in a beaker, preparing a silane-modified liquid with a volume concentration of 3%, and soaking the biochar-bentonite loaded sponge in the above 3% silane-modified liquid for 2 hours to obtain a hydrophobic and lipophilic sponge material loaded with biochar and bentonite.

[0058] Example 3

[0059] Step (1), cutting a commercially available polyurethane sponge into a 2×2×1 cm rectangular block, then ultrasonically cleaning the sponge twice in anhydrous ethanol and deionized water, and after cleaning, drying the cleaned polyurethane sponge in a 60° C. oven for 10 h.

[0060] Step (2), adding 0.05 g of dopamine hydrochloride to 50 mL of 20 mmol / L Tris alkaline buffer solution, adjusting the pH value of the solution to 9.0, to obtain a dopamine hydrochloride-Tris solution; then soaking the cleaned polyurethane sponge in the dopamine hydrochloride-Tris solution at room temperature for 15 hours. After the soaking is completed, taking out the polyurethane sponge, and rinsing the unreacted dopamine with ultrapure water to obtain a dopamine-coated polyurethane sponge.

[0061] Step (3), sintering fir wood chips at 600°C and passing through a 200-mesh sieve to obtain fir wood chip biochar; dissolving 50 g of natural sodium bentonite in 700 mL of ultrapure water, stirring continuously for 3 hours to uniformly disperse it to form a suspension, and after the stirring is completed, the bentonite suspension is allowed to stand for 30 minutes. After the standing is completed, the upper suspension is centrifuged. After the centrifugation is completed, the precipitate is placed at 60°C for drying. After the drying is completed, the precipitate is crushed and passed through a 200-mesh sieve to obtain purified sodium bentonite.

[0062] Step (4), adding fir sawdust biochar and purified sodium bentonite in a mass ratio of 1:1 to 50 mL of ultrapure water for mechanical mixing, stirring at room temperature for 2 hours to obtain a uniformly dispersed biochar-bentonite mixture; immersing a dopamine-coated polyurethane sponge in the biochar-bentonite mixture, squeezing out the solution after the sponge is saturated with adsorption, and repeating this immersion-extrusion process 5 times; the sponge after immersion-extrusion is placed in a 60°C oven and dried for 10 hours to obtain a biochar-bentonite loaded sponge.

[0063] Step (5), measure 1 mL of dodecyltrimethoxysilane and 49 mL of anhydrous ethanol in a beaker to prepare a silane-modified liquid with a volume concentration of 2%, and soak the biochar-bentonite loaded sponge in the above 2% silane-modified liquid for 2 hours to obtain a hydrophobic and lipophilic sponge material loaded with biochar and bentonite.

[0064] Example 4

[0065] Step (1), cutting a commercially available polyurethane sponge into a 2×2×1 cm rectangular block, then ultrasonically cleaning the sponge in anhydrous ethanol and deionized water for 3 times, and after cleaning, drying the cleaned polyurethane sponge in a 55° C. oven for 10 h.

[0066] Step (2), adding 0.05 g of dopamine hydrochloride to 50 mL of 10 mmol / L Tris alkaline buffer solution, adjusting the pH value of the solution to 8.5, to obtain a dopamine hydrochloride-Tris solution; then soaking the cleaned polyurethane sponge in the dopamine hydrochloride-Tris solution at room temperature for 10 hours, after the soaking is completed, taking out the polyurethane sponge, and rinsing the unreacted dopamine with ultrapure water to obtain a dopamine-coated polyurethane sponge.

[0067] Step (3), sintering fir wood chips at 400°C and passing through a 200-mesh sieve to obtain fir wood chip biochar; dissolving 50 g of natural sodium bentonite in 700 mL of ultrapure water, stirring continuously for 3 hours to disperse it evenly to form a suspension, and after the stirring is completed, the bentonite suspension is allowed to stand for 30 minutes. After the standing is completed, the upper suspension is centrifuged. After the centrifugation is completed, the precipitate is placed at 60°C for drying. After the drying is completed, the precipitate is crushed and passed through a 200-mesh sieve to obtain purified sodium bentonite.

[0068] Step (4), adding fir sawdust biochar and purified sodium bentonite in a mass ratio of 1:4 into 50 mL of ultrapure water for mechanical mixing, stirring at room temperature for 2 hours to obtain a uniformly dispersed biochar-bentonite mixture; immersing a dopamine-coated polyurethane sponge in the biochar-bentonite mixture, squeezing out the solution after the sponge is saturated with adsorption, and repeating this immersion-extrusion process 5 times; the sponge after immersion-extrusion is placed in a 60° C. oven and dried for 10 hours to obtain a biochar-bentonite loaded sponge.

[0069] Step (5), measure 1 mL of methyltrimethoxysilane and 49 mL of anhydrous ethanol in a beaker to prepare a silane-modified liquid with a volume concentration of 2%, and soak the biochar-bentonite loaded sponge in the above 2% silane-modified liquid for 2 hours to obtain a hydrophobic and lipophilic sponge material loaded with biochar and bentonite.

[0070] Comparative Example 1

[0071] Step (1), cutting a commercially available polyurethane sponge into a 2×2×1 cm rectangular block, then ultrasonically cleaning the sponge in anhydrous ethanol and deionized water for 3 times, and after cleaning, drying the cleaned polyurethane sponge in a 60° C. oven for 10 h.

[0072] Step (2), adding 0.05 g of dopamine hydrochloride to 50 mL of 10 mmol / L Tris alkaline buffer solution, adjusting the pH value of the solution to 8.5, to obtain a dopamine hydrochloride-Tris solution; then soaking the cleaned polyurethane sponge in the dopamine hydrochloride-Tris solution at room temperature for 12 hours, after the soaking is completed, taking out the polyurethane sponge, and rinsing the unreacted dopamine with ultrapure water to obtain a dopamine-coated polyurethane sponge.

[0073] Comparative Example 2

[0074] Step (1), cutting a commercially available polyurethane sponge into a 2×2×1 cm rectangular block, then ultrasonically cleaning the polyurethane sponge in anhydrous ethanol and deionized water for 3 times, and after cleaning, drying the cleaned polyurethane sponge in a 60° C. oven for 10 h.

[0075] Step (2), calcining fir sawdust at 400°C and passing through a 200-mesh sieve to obtain fir sawdust biochar; dissolving 50 g of natural sodium bentonite in 700 mL of ultrapure water, stirring continuously for 3 hours to disperse it evenly to form a suspension, and after the stirring is completed, the bentonite suspension is allowed to stand for 30 minutes. After the standing is completed, the upper suspension is centrifuged. After the centrifugation is completed, the precipitate is placed at 60°C for drying. After the drying is completed, the precipitate is crushed and passed through a 200-mesh sieve to obtain purified sodium bentonite.

[0076] Step (3), adding fir sawdust biochar and purified sodium bentonite in a mass ratio of 1:1 to 50 mL of ultrapure water for mechanical mixing, stirring at room temperature for 2 hours to obtain a uniformly dispersed biochar-bentonite mixture; immersing a dopamine-coated polyurethane sponge in the biochar-bentonite mixture, squeezing out the solution after the sponge is saturated with adsorption, and repeating this immersion-extrusion process 5 times; placing the sponge after immersion-extrusion in an oven at 60° C. and drying it for 10 hours to obtain a biochar-bentonite loaded sponge.

[0077] Step (4), measure 0.5 mL HDTMS and 49.5 mL anhydrous ethanol in a beaker to prepare a silane modification solution with a volume fraction of 1%, and soak the biochar-bentonite loaded sponge in the 1% HDTMS modification solution for 2 hours to obtain a hydrophobic and lipophilic sponge material loaded with biochar and bentonite.

[0078] Comparative Example 3

[0079] The same as Example 1, except that in step (3), no purified sodium bentonite is prepared, and in step (4), the fir sawdust biochar and natural sodium bentonite are directly mixed in a mass ratio of 1:1.

[0080] Comparative Example 4

[0081] The same as Example 1, except that no silane coupling agent modification was performed, and the biochar-bentonite loaded sponge obtained in step (4) was the final product.

[0082] Comparative Example 5

[0083] The same as Example 1, except that the fir sawdust biochar was replaced with corn straw biochar (the corn straw biochar was purchased from Henan Jiahe Water Purification Materials Co., Ltd.).

[0084] The sponge oil-absorbing materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5 were used for adsorption of n-hexane, cyclohexane, dichloromethane and engine oil (a certain mass of sponge material (recorded as m1) was weighed and placed in a beaker filled with oil. After adsorption for 10 seconds, the sponge was taken out with tweezers and the oil droplets were allowed to fall naturally. After the sponge material stopped dripping oil, it was weighed (recorded as m2). The oil absorption of the sponge material was calculated according to the formula ε=((m2-m1)) / m1). The saturated oil absorption of the sponge oil-absorbing materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5 is shown in Table 1.

[0085] Since the oil absorbing material will eventually be put into the actual environment for oil-water adsorption separation, the pH of the actual water body may vary greatly due to the influence of the leaked chemicals. Therefore, the corrosion resistance of the hydrophobic and oleophilic sponge oil absorbing material loaded with biochar and bentonite prepared in Example 1 of the present invention was tested in a wide pH range (1-13). Figure 4 As shown, after the sponge oil-absorbing material was completely immersed in solutions of different pH values ​​for 24 hours, the contact angle remained at about 128°, indicating that the acid and alkali had no effect on the coating, and the modified sponge still had good hydrophobic and lipophilic properties.

[0086] The hydrophobic and oleophilic sponge oil-absorbing material loaded with biochar and bentonite prepared in Example 1 of the present invention was tested for its reusability (the organic solvent absorbed in the sponge oil-absorbing material was discharged by mechanical extrusion, and then washed and dried. The adsorption saturation was extruded and discharged, and the oil was re-adsorbed after drying as one cycle to investigate the change of adsorption capacity with the number of cycles). The results are as follows Figure 5 As shown by Figure 5 It can be seen that the adsorption amount of n-hexane by the sponge does not change much with the increase of the number of cycles, indicating that the prepared sponge oil-absorbing material loaded with biochar and bentonite has good recyclability.

[0087] Table 1 Saturated oil absorption of sponge oil-absorbing materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5

[0088]

[0089] As can be seen from Table 1, due to the bonding effect of polydopamine, the fir sawdust biochar and purified bentonite are firmly loaded on the sponge material. The loaded biochar and bentonite can increase the surface roughness of the sponge and increase its surface area. The bentonite and biochar in Example 4 are tightly combined, which greatly improves the adsorption performance of the sponge. Therefore, the sponge oil-absorbing material loaded with biochar and bentonite prepared in Example 4 has the best adsorption effect; Compared with Example 1, Comparative Example 1 only coats the polyurethane sponge with dopamine. Although the hydrophobicity of the sponge surface can be improved, it only has surface adhesion, and the surface area of ​​the sponge is not increased, so the oil absorption is relatively large. Low; Compared with Example 1, in Comparative Example 2, dopamine was not coated before loading biochar and bentonite, and biochar and bentonite were not firmly loaded on the sponge material, so the oil absorption was slightly lower than that of Example 1; Compared with Example 1, in Comparative Example 3, bentonite was not purified, so the adsorption performance of bentonite was not improved, thereby reducing the oil absorption of the material; Compared with Example 1, Comparative Example 4 was not silane-modified, so the sponge material absorbed both water and oil, and had no hydrophobic and lipophilic selective adsorption; Compared with Example 1, corn straw biochar was added in Comparative Example 5, and biochar was not well combined with bentonite, thereby reducing the oil absorption of the sponge. It can be seen from Examples 1 and 4 that the combination of biochar and bentonite can improve the adsorption performance of the material, but the specific effect also needs to consider the influence of factors such as the ratio of biochar to bentonite and the preparation method. Bentonite has a large number of layered structures and microporous structures, which can provide a large number of adsorption sites and adsorption surfaces, and has good adsorption performance. Biochar has a high specific surface area and rich functional groups, and also has good adsorption properties. The mass ratio of 1:4 between biochar and bentonite is well combined, so the adsorption performance of the sponge is also enhanced accordingly. The above data show that polydopamine is a good platform for modifying the surface of materials or for fixing functional groups or nanoparticles.

[0090] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. Application of a sponge oil-absorbing material loaded with biochar and bentonite in oil-water separation, characterized in that: The pH of water is 1 to 13; The preparation method of the sponge oil-absorbing material loaded with biochar and bentonite is as follows: using polyurethane sponge as a matrix, modifying it with dopamine hydrochloride, then loading biochar and bentonite, and modifying it with a silane coupling agent to obtain the sponge oil-absorbing material loaded with biochar and bentonite; The process of loading biochar and bentonite is as follows: adding biochar and bentonite into water, mixing to obtain a biochar-bentonite mixed solution, immersing a dopamine-coated polyurethane sponge in the biochar-bentonite mixed solution, squeezing out the solution after the sponge is saturated with adsorption, and repeating this immersion-extrusion process 3 to 5 times; drying the sponge after immersion-extrusion at 50 to 60° C. for 10 to 12 hours to obtain a biochar-bentonite loaded sponge; The biochar is fir sawdust biochar, and the bentonite is purified sodium-based bentonite; The preparation method of the purified sodium bentonite is as follows: 50-100 g of natural sodium bentonite is dissolved in 500-800 mL of ultrapure water, and the mixture is continuously stirred for 2-4 hours to disperse the mixture evenly to form a suspension; after the stirring, the bentonite suspension is allowed to stand for 20-40 minutes, and after the standing, the upper suspension is centrifuged; after the centrifugation, the precipitate is dried at 50-60° C., and after the drying, the precipitate is crushed and sieved through a 100-200 mesh sieve to obtain the purified sodium bentonite.

2. The use according to claim 1, characterized in that: Before the polyurethane sponge is modified with dopamine hydrochloride, it is pretreated. The pretreatment process is as follows: the polyurethane sponge is ultrasonically cleaned 2 to 4 times in anhydrous ethanol and deionized water in turn. After the cleaning, the cleaned polyurethane sponge is dried at 50 to 60° C. for 10 to 12 hours.

3. The use according to claim 2, characterized in that: The process of modification using dopamine hydrochloride is as follows: adding dopamine hydrochloride to an alkaline buffer solution, adjusting the pH value of the solution to 8.0-9.0, and obtaining a dopamine hydrochloride-alkaline buffer solution; then soaking the pretreated polyurethane sponge in the dopamine hydrochloride-alkaline buffer solution at room temperature for 10-20 hours, and after the soaking is completed, taking out the polyurethane sponge, and rinsing the unreacted dopamine hydrochloride with ultrapure water to obtain a dopamine-coated polyurethane sponge.

4. The use according to claim 3, characterized in that: The material-liquid ratio of dopamine hydrochloride to alkaline buffer solution is (0.01-0.05) g: (50-100) mL; The alkaline buffer solution is a tris(hydroxymethyl)aminomethane buffer solution with a concentration of 10-20 mmol / L.

5. The use according to claim 1, characterized in that: The mass ratio of biochar to bentonite is 1:1 to 1:

5.

6. The use according to claim 1, characterized in that: The process of modification with silane coupling agent is as follows: soak the biochar-bentonite loaded sponge in silane coupling agent for 1 to 2 hours to obtain the sponge oil-absorbing material loaded with biochar and bentonite.

7. The use according to claim 6, characterized in that: The silane coupling agent is one of hexadecyltrimethoxysilane, dodecyltrimethoxysilane, methyltrimethoxysilane and trichlorooctadecylsilane, and the volume concentration of the silane coupling agent is 0.5-3%.

Citation Information

Patent Citations

  • Super-hydrophobic polyurethane sponge as well as preparation method and application thereof

    CN114437402A